Efficacy and safety of different ticagrelor regimens versus clopidogrel in patients with coronary artery disease: a retrospective multicenter study (SUPERIOR). (2nd January 2021) - Shi, Jing; He, Meijiao; Wang, Wennan; Liu, Guangzhong; Zhang, Haiyu; Sun, Danghui; Li, Jianqiang; Mu, Hongyuan; Xu, Minglu; Zhao, Chenyang; Wang, Jiayu; Zhang, Chongyang; et al.
Abstract: Current guidelines favor dual anti-platelet therapy with ticagrelor 90 mg BID (T90BID) over clopidogrel 75 mg QD (C75QD) in addition to aspirin for acute coronary syndrome. However, an increased risk of ticagrelor-related adverse events prompted the evaluation of low-dose regimens. This study (NCT03381742) retrospectively analyzed the data from 11 hospitals on 3, 043 patients with coronary artery disease, who received C75QD, T90BID, ticagrelor 45 mg BID (T45BID), or ticagrelor 90 mg QD (T90QD). Compared with C75QD, both T45BID and T90QD showed significantly higher inhibition of platelet aggregation ( P < .0001) and lower platelet-fibrin clot strength ( P < .0001) induced by adenosine diphosphate. Furthermore, compared with T90BID, two low-dose regimens had a much lower minor bleeding rate and a significantly higher proportion of patients within the therapeutic window for P2Y12 receptor reactivity. There were no significant differences between T45BID and T90QD in the trough plasma concentrations of ticagrelor and its active metabolite. Similar efficacy and safety outcomes were observed in the propensity score-matched analysis. In conclusion, the low-dose ticagrelor regimen, either T45BID or T90QD, may provide a more attractive benefit-risk profile than C75QD or T90BID.